2021
DOI: 10.3390/foods10020353
|View full text |Cite
|
Sign up to set email alerts
|

Chinese Consumers’ Attitudes and Potential Acceptance toward Artificial Meat

Abstract: The interest for artificial meat has recently expanded. However, from the literature, perception of artificial meat in China is not well known. A survey was thus carried out to investigate Chinese attitudes toward artificial meat. The answers of 4666 respondents concluded that 19.9% and 9.6% of them were definitely willing and unwilling to try artificial meat respectively, whereas 47.2% were not willing to eat it regularly, and 87.2% were willing to pay less for it compared to conventional meat. Finally, 52.9%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
82
4
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 89 publications
(98 citation statements)
references
References 53 publications
9
82
4
3
Order By: Relevance
“…It is likely that respondents with low income hope to have access to a cheapest protein food in the future, whereas richer respondents are not willing to pay for this novel food product, despite earning more money per month. In contrast, in the study of Liu et al [35], Chinese young people, who are beginners in being economically independent, being still students, may tend to be more conservative (i.e., with lowest WTT, WTE, and WTP) towards new products, especially if the price of the new product is too high.…”
Section: "Cell-based Meat" Is More Attractive To People With Low Income In Brazilmentioning
confidence: 79%
See 2 more Smart Citations
“…It is likely that respondents with low income hope to have access to a cheapest protein food in the future, whereas richer respondents are not willing to pay for this novel food product, despite earning more money per month. In contrast, in the study of Liu et al [35], Chinese young people, who are beginners in being economically independent, being still students, may tend to be more conservative (i.e., with lowest WTT, WTE, and WTP) towards new products, especially if the price of the new product is too high.…”
Section: "Cell-based Meat" Is More Attractive To People With Low Income In Brazilmentioning
confidence: 79%
“…Moreover, younger respondents are more concerned about the ethical and environmental issues related to animal husbandry, and tend to think of "cell-based meat" in terms of their own consumption, whereas older people tend to think of it in terms of an implicit societal transition (for review: [47]). This is not the case for older Chinese respondents (>51 years of age) who are more willing to engage with "cell-based meat", unlike younger people [35].…”
Section: Hierarchical Classifications Of Quantitative and Qualitative Variables And Respondentsmentioning
confidence: 93%
See 1 more Smart Citation
“…The sensory experience of cultured meat may additionally be affected by certain attributes to be selected for in cell lines. Consumer surveys have found that many consumers expect cultured meat to be less tasty than conventional meat, and this perception contributes to their unwillingness to consume cultured meat [ 11 , 12 ]. The sensory experience of meat generally involves taste and aroma from the Maillard reaction and lipid oxidation reactions, color from heme proteins, and a tender, juicy texture [ 85 ].…”
Section: Unique Challenges For Cell Lines Used In Cellular Agriculturementioning
confidence: 99%
“…Past research has found that consumers expect cultured meat to taste worse than conventional meat, and that taste is essential for the long-term acceptance of cultured meat [ 11 ]. Taste, nutrition, and safety have been shown in consumer studies to be important concerns for the willingness to consume cultured meat [ 11 , 12 ]. Immortal cell lines used in cultured meat should therefore be developed from cell types and species familiar to consumers and that are tasty, nutritious, and food-safe.…”
Section: Introductionmentioning
confidence: 99%